Improving obturator retention in hollow palatal defect using silicone soft-reliner - Yuwono, William; Endang Wahyuningtyas; Intan Ruspita; Suparyono Saleh (Indonesian Journal of Prosthodontic, 2025)
Defect in the intraoral maxilla or palate resulting from surgical hemimaxillectomy can lead to difficulties in chewing, speaking, swallowing, and may also affect psychological function. One effective rehabilitation method for restoring oral function is the obturator prosthesis. This case report discusses the rehabilitation of a palatal defect following hemimaxillectomy, utilizing a hollow bulb obturator with a silicone-based soft liner and incorporating extracted posterior teeth as immediate dental provisions for relining an interim denture. The patient, a 46-year-old male, presented at Universitas Gadjah Mada Dental Hospital with complaints of discomfort, instability, and inadequate palatal coverage from his prosthetic obturator after undergoing tumor removal in the right maxillary area two years earlier. Examination revealed a significant hollow defect under the palate, exposure of the inferior nasal conchae, and mobility in the first and second premolars on the right side. Panoramic radiographs indicated loss of ridge support around these teeth. To enhance retention and comfort, a silicone-based soft liner was applied to the obturator. The use of extracted teeth proved beneficial for improving occlusal force, strength, and aesthetics. Thus, a hollow ground obturator with a soft reliner is recommended for effective rehabilitation post Class II Aramany hemimaxillectomy. Keywords: Palatum defect, Obturator, Hollow bulb, Soft-reliner